Identity as not-(im)possibilities of an interreligious dialogue from the fringes exploring Giorgio Agamben and the interreligious dialogue - Maltese, Giovanni (Silliman Journal, 2010)
The present essay explores if and how selected political concepts developed by the philosopher Giorgio Agamben can be applied to difficulties frequently met in interreligious encounters. Using Agamban concepts such as "Homo Sacer"and "The Cot of Apelles", this paper discusses problems of representation, identity and inclusion/exclusion, which are structurally inherent in interreligious dialogues. The essay concludes sketching the potential of Agamben's category of "messianic-suspended identity"in connection with a method of radical historization for the interreligious dialogue.